Практическое применение всережимного моделирующего комплекса электроэнергетических систем - Андреев М. В. Михаил Владимирович; Боровиков Ю. С. Юрий Сергеевич; Гусев А. С. Александр Сергеевич; Сулайманов А. О. Алмаз Омурзакович; Суворов А. А. Алексей Александрович; Рубан Н. Ю. Николай Юрьевич; Уфа Р. А. Руслан Александрович (2017, 2017)
Заглавие с экрана